Effect of intra-articular corticosteroid injections for knee osteoarthritis on the rates of subsequent knee replacement and post-operative outcomes: a national cohort study of England - Samuel Hawley; Albert Prats-Uribe; Gulraj S. Matharu; Antonella Delmestri; Daniel Prieto-Alhambra; Andrew Judge; Michael R. Whitehouse (BMC Medicine)
Abstract Background Intra-articular corticosteroid injection (IACI) is an established treatment option for uncontrolled pain in osteoarthritis. There is a lack of longer-term follow-up in most studies of the effects of IACI, meaning there is scarcity of data on the impact of IACI on the subsequent need for joint replacement. Our aim was to assess the effect of IACI for knee osteoarthritis on the subsequent incidence of knee replacement surgery and on associated post-operative outcomes. Methods We conducted a cohort study of knee osteoarthritis patients registered in the Clinical Practice Research Datalink (CPRD) GOLD database with an incident diagnosis between 2005 and 2019. Exposure was single or repeated IACI use, analysed separately. The primary outcome was knee replacement during 1-year and 5-year follow-ups. Secondary outcomes included post-operative patient-reported outcome measures and adverse events. Primary analyses used general practitioner practice preference for IACI as an instrumental variable given this methodology can account for strong and unmeasured confounding. Secondary analyses used propensity score matching, accounting for measured covariates only. Results During 1-year follow-up, 1628/33,357 (4.9%) knee osteoarthritis patients underwent knee replacement, for which single IACI was associated with lower risk, which persisted to 5-year follow-up (incidence rate ratio: 0.52 [0.36, 0.77]). Conversely, in secondary propensity score analyses no association was found between IACI use and knee replacement rate at 1-year follow-up, and an estimated increased rate of knee replacement at 5-year follow-up. Use of IACI pre-joint replacement was not associated with any adverse post-operative outcomes, for example, 1-year complication rates (per 100 person-years) following knee replacement were 4.6 (3.8, 5.8), 4.0 (2.7, 6.0) and 5.0 (3.1, 8.1) among patients with no, single and repeat pre-joint replacement IACI use, respectively. Conclusions Findings from our main analysis suggest that short-term pain reduction following IACI for knee osteoarthritis may translate to lower rates of knee replacement over 5 years follow-up, although contradictory associations were observed in secondary analyses which likely reflected residual confounding by indication. Reassuringly, IACI use before knee replacement was not associated with post-operative adverse outcomes.